2022
DOI: 10.15826/jtr.2022.8.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Analyze the impact of the transition from business tax to VAT on the tax burden of transport enterprises in various regions of China

Abstract: In recent years, the transportation industry has enjoyed the benefits brought about by changes in the national tax policy. The purpose of this paper is to analyze the impact of the change from Business Tax to Value-Added Tax (BT-to-VAT) on the tax burden of transport enterprises in various regions of China. Based on the cross-regional characteristics of the transportation industry, China is divided into four regions: eastern, central, western and northeast. Research hypothesis – the tax reduction effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…Wagner AF et al [ 36 ] suggested that implementing tax cuts for firms with a higher tax burden can lead to more benefits. Ma J et al [ 37 ] used the difference-in-difference (DID) method with data covering 22 listed companies from 2009 to 2020, and the empirical study showed that BT to VAT reduces the tax burden of companies. Isik S, Özbuğday FC [ 38 ] tested whether tax cuts would reduce fertilizer prices by DID and the results showed that consumers would benefit from the tax cuts.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Wagner AF et al [ 36 ] suggested that implementing tax cuts for firms with a higher tax burden can lead to more benefits. Ma J et al [ 37 ] used the difference-in-difference (DID) method with data covering 22 listed companies from 2009 to 2020, and the empirical study showed that BT to VAT reduces the tax burden of companies. Isik S, Özbuğday FC [ 38 ] tested whether tax cuts would reduce fertilizer prices by DID and the results showed that consumers would benefit from the tax cuts.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…El cumplimiento tributario se define como algo complejo que se ve desde muchas perspectivas. Ma et al (2022) afirmó que el cumplimiento tributario significa reportar ingresos de acuerdo con las normas tributarias, reportar declaraciones de impuestos y pagar impuestos de manera oportuna. Okpeyo et al (2019a) mencionaron que puede definirse como una situación en la que los contribuyentes ejercen sus derechos tributarios y cumplen con sus obligaciones tributarias.…”
Section: Cumplimiento Tributariounclassified
“…Las sanciones tributarias como garantía de lo dispuesto en las normas tributarias o normas tributarias deben ser acatadas para que los contribuyentes continúen con lo dispuesto en las normas (Ma et al, 2022). Las sanciones administrativas y las sanciones penales están destinadas a que en el futuro los contribuyentes no vuelvan a cometer los mismos errores.…”
Section: Efecto De La Sanción En La Conciencia Tributariaunclassified
“…China's dependence on imports of oil and natural gas has increased year by year, and has risen to 73% and 43% in 2020. At the same time, automobiles are the main contributor to the total pollutant emissions [1]. The emergence of alternative fuel vehicles can make a significant contribution to solving resource and environmental protection problems, and the government has also actively launched various preferential policies to support it.…”
Section: Introductionmentioning
confidence: 99%